Dexamethasone Intravitreal Implant for the Treatment of Macular Edema Following Retinal Vein Occlusion: Post Hoc Analysis of Post-Marketing Surveillance Data in the Real-World Setting in Korea - Kim MS (Dove Medical Press, 2021)
Min Seok Kim,1 Jasmine Choi,2 Hyeong Du Lee,3 Se Joon Woo1 On behalf of the Korea Ozurdex Post-Marketing Surveillance Study Group1Department of Ophthalmology, Seoul National University College of Medicine, Seoul National University Bundang Hospital, Seongnam, Korea; 2Allergan, an AbbVie Company, Irvine, CA, USA; 3Allergan, an AbbVie Company, Seoul, KoreaCorrespondence: Se Joon WooDepartment of Ophthalmology, Seoul National University College of Medicine, Seoul National University Bundang Hospital, 173-82 Gumi-ro, Bundang-gu, Seongnam-si, Gyeonggi-do, 13620, Republic of KoreaTel +82-31-787-7377Fax +82-31-787-4057Email sejoon1@snu.ac.krPurpose: To supplement established efficacy and safety data, this analysis evaluated the real-world use of dexamethasone (DEX) intravitreal implant 700 μg for retinal vein occlusion (RVO)-related macular edema in an Asian population and baseline factors potentially associated with DEX implant efficacy.Patients and Methods: A prospective, observational, post-marketing surveillance study was conducted at 38 sites in South Korea in patients consecutively presenting with macular edema following branch or central RVO (BRVO, CRVO), and administered a first DEX implant. Follow-up visits and subsequent DEX or other therapies conformed with local practice. Outcome measures included best-corrected visual acuity (BCVA), change in BCVA from baseline, responder rates, and adverse events. Associations between baseline characteristics and BCVA gains were evaluated. Month-1, -2, -4, and -6 visit analysis windows were established.Results: In all, 700 patients (79.1% BRVO, 20.9% CRVO) received 1.12 DEX implants (mean) and were followed for 101.5 days (standard deviation, 51.7); 90% received a single implant. Among patients with analyzable data, mean BCVA improved from baseline with peak changes in Month 2 of − 0.193 and − 0.212 LogMAR, (P < 0.0001) and remained significant in the BRVO subgroup at the Month 4 and 6 windows (P < 0.0001 and P = 0.0039, respectively). Treatment-naïve patients experienced greater BCVA increases. The proportion of patients with stable/improved BCVA tended to decrease after Month 2 through Month 6 and the decline was greater in the CRVO subgroup. At the Month-2 window, ≥ 1-, 2- and 3-line increases were positively associated with younger age, worse baseline BCVA, and treatment naivety. The most common adverse event was increased intraocular pressure.Conclusion: In the real-world clinical setting in South Korea, DEX implant improved visual acuity and had a favorable safety profile similar to that reported in randomized controlled trials and observational European and North American studies. These data further support the value of DEX implant as a treatment option for RVO.ClinicalTrials.gov Identifier: NCT01976650. Date of registration: November 6, 2013.Keywords: retinal vein occlusion, dexamethasone, intravitreal, implant, post-marketing, real world